Maya and Catholic cultures in crisis - Early, John D. (University Press of Florida, 2012)
A description of the confrontation in Maya communities in the latter part of the 20th century between Maya and Catholic theological worldviews in crisis. The Mayans' loss of land and extreme poverty brought their theology into question since the covenant with their gods was supposed to protect their communities, but the Catholic Church's attempt to evangelize them according to the Catholic worldview formulated by the 16th century Council of Trent did little to alleviate the crisis.